Culturally Tailored Nutrition and Lifestyle Intervention can Effectively Reduce the Cardio-Metabolic Risk Factors in Korean Migrants Living in Australia - (Hedy) Sung Hyunsin; Antonas Kiriakos; Su Xiao (International Journal of Nutrition, 2015)
The risk levels of chronic diseases are increasing among Asian migrants in Western countries compared to their origin-country counterparts. This study evaluates the impact of an 8-week nutrition and lifestyle intervention on cardio-metabolic risk factors in Korean migrants living in Melbourne, Australia. Thirty participants aged 32-62 years completed the program. Self-reported food intake and physical activity, anthropometric and blood pressure measurements, and biomarkers of cardio-metabolic risk were assessed. An initial training session and four consequent nutrition advice sessions were provided for all participants. There was a significant reduction in the waist and hip circumferences. Positive changes were also observed in plasma lipid profiles, calcium intake and frequency of physical activities. These findings demonstrate that a culturally appropriate nutrition and lifestyle intervention can be successfully delivered to reduce the cardio-metabolic risk factors and improve the health and wellbeing of Korean adult migrants.
Keywords: Korean migrants